2001
DOI: 10.1067/mcp.2001.113183
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics and metabolic disposition of tacrolimus: A comparison across ethnic groups

Abstract: Significant differences in tacrolimus pharmacokinetics exist among the three different ethnic groups. Our results indicate that this may result from differences in intestinal CYP3A or P-glycoprotein activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
123
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(132 citation statements)
references
References 28 publications
5
123
2
Order By: Relevance
“…Significant differences in the tacrolimus pharmacokinetic profile have been found in various ethnic groups. The mean tacrolimus dose is 96% higher in African American transplant recipients than in Caucasians or Asians (25,26). Maintenance of adequate levels of tacrolimus and cyclosporine is a critical issue in these patients (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Significant differences in the tacrolimus pharmacokinetic profile have been found in various ethnic groups. The mean tacrolimus dose is 96% higher in African American transplant recipients than in Caucasians or Asians (25,26). Maintenance of adequate levels of tacrolimus and cyclosporine is a critical issue in these patients (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated the contribution of the recipient CYP3A5 genotype on tacrolimus metabolism. Mancinelli et al (2001) found that tacrolimus pharmacokinetics were affected by differences of the intestine CYP3A5 genotype. A significant difference was also found in tacrolimus daily dose and tacrolimus C/D ratios between recipients carrying the CYP3A5 6986GG allele and recipients carrying the CYP3A5 6986AG/AA allele both at 2 and 3 weeks and 1 month after transplantation (Uesugi et al, 2006).…”
Section: Influence Of Age Time Course and Graft Liver Weight On Thementioning
confidence: 99%
“…Recent developments have improved understanding of the molecular mechanisms responsible for such interethnic differences. Genetic variations that may provide a molecular basis for ethnic differences in drug metabolizing enzymes (CYP 2C9 (4), 2C19 (5), 2D6 (6), and 3A4 (7)), drug transporter (Pglycoprotein (8), alpha-1 acid glycoprotein (9)), and drug receptors (adrenoceptors (10)). Their relevance for the clinical evaluation of drugs is attracting growing attention, especially, since the discussion on the acceptability of foreign clinical data has been set by the International Conference on Harmonization (11,12).…”
Section: Introductionmentioning
confidence: 99%